Using forum theatre in moral reasoning study among form four students - Thambu, N.; Balakrishnan, Vishalache (2014)
Raising the dimension of moral reasoning, is still a major challenge in teaching and learning of Moral Education in Malaysia. Previous studies show a variety of techniques and strategies have been used to instil moral reasoning skills among students. One way of working creatively to raising the moral reasoning of students is through a technique called Forum Theatre. Using an action research design, this paper aims is to explain how the use of Forum Theatre can playa role in developing a moral reasoning among secondary school students. The four stages of Forum Theatre were used in Moral Education classes. The result of this study support previous literature demonstrating that Forum Theatre gives room for the development of moral reasoning. The process of moral reasoning among students involves three developmental reasoning elements which are reasonable thought, careful consideration in "decision making" and justification for the action taken.